2008
DOI: 10.1029/2008gl034337
|View full text |Cite
|
Sign up to set email alerts
|

Episodic growth of fault‐related fold in northern Japan observed by SAR interferometry

Abstract: The interferometric analysis using ALOS SAR data allows us to map the detailed spatial pattern of the deformation associated with the 2007 M6.8 Niigataken Chuetsu‐oki earthquake. The interferograms reveal not only a large deformation near the source area of the earthquake but also a local uplift in the region of active folding, 15 km east of the earthquake epicenter. The 1.5‐km‐wide and 15‐km‐long band of uplift is located along the anticline axis of an active fold and cannot be explained by the elastic deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
0
17
1
Order By: Relevance
“…3(b)). The Geographical Survey Institute of Japan (GSI) found that the anticline was located in the area compressed by the earthquake and proposed that it was uplifted by the compression (Nishimura et al, 2008). Similar fold deformation associated with an earthquake was also found at the earthquake site in southeast Iran (Fielding et al, 2004), and it would relate to the growth of a fold.…”
Section: Crustal Deformation Obtained By Palsar Insarmentioning
confidence: 90%
“…3(b)). The Geographical Survey Institute of Japan (GSI) found that the anticline was located in the area compressed by the earthquake and proposed that it was uplifted by the compression (Nishimura et al, 2008). Similar fold deformation associated with an earthquake was also found at the earthquake site in southeast Iran (Fielding et al, 2004), and it would relate to the growth of a fold.…”
Section: Crustal Deformation Obtained By Palsar Insarmentioning
confidence: 90%
“…2d), has in some cases been found to be associated with creep along shallow faults, caused by changes in the local stress field due to co-seismic slip on adjacent faults (Nishimura et al 2008;Copley & Reynolds 2014;Fattahi et al 2015;Copley & Jolivet 2016). The InSAR observations at Bam indicate that parts of the Bam-Baravat Fault began creeping after the 2003 earthquake (see Fig.…”
Section: G Ro W T H O F T H E B a M -B A R Avat R I D G E A N D L I Tmentioning
confidence: 99%
“…However, Fujiwara et al (2000a, b), Fukushima et al (2013), Guerrieri et al (2010), Nishimura et al (2008) and Wei et al (2011) reported that lineaments representing small displacements appear on interferograms, and Oskin et al (2012) reported that small displacements appear in differential LiDAR images.…”
Section: Introductionmentioning
confidence: 99%